Moments of meeting : Buber, Rogers, and the potential for public dialogue - Cissna, Kenneth N. (SUNY series in communication studies., 2002)
"Moments of Meeting tells the story of a uniquely important event in twentieth-century intellectual history, the 1957 public dialogue of philosopher Martin Buber and psychotherapist Carl Rogers, and explores the practical implications of that event for contemporary social and cultural theory. Supported by original historical research, close textual analysis, and a variety of interviews, the book illuminates the careers, theories, and practices of two of the last century's foremost scholars of dialogue, while it clarifies what they shared in common. Following a careful case study of the Buber-Rogers public conversation about the dynamics of dialogue itself, the authors conclude that public dialogue cannot be built primarily upon skillful technique. Instead, we must support settings and attitudes that enable unique "moments of meeting.""--Jacket